Introduction to NJWLS 2020-1 - Buch, Anders (Nordic Journal of Working Life Studies, 2020)
This issue of Nordic Journal of Working Life Studies collects four new articles. In Cultural Obstacles in Transnational Trade Union Cooperation in Europe, Bengt Larsson aims to understand cultural differences that are seen as obstacles to cooperation by trade union representatives. Based on 38 interviews with 46 trade union officials from nine European countries, Larsson identifies the major cultural obstacles for cooperation. Even though noncultural factors – such as financial and network resources, different priorities, and differences in national labor market policies and regulations – are major obstacles for successful cooperation among trade unions, cultural factors play an important role in hampering cooperation. With inspiration from neo-institutional theory and organization theory, Larsson conceptualizes union culture in relation to norms, values, and meanings drawn from broader society. The findings of the study point to language and translation issues, differences experienced in cultural values and everyday practices, and differences in issues relating to ideology and identity regarding member orientation, negotiation, mobilization of members, etc. (...)